Important Ice Processes Are Missed by the Community Earth System Model in Southern Ocean Mixed‐Phase Clouds: Bridging SOCRATES Observations to Model Developments. Issue 4 (14th February 2023) - Zhao, Xi; Liu, Xiaohong; Burrows, Susannah; DeMott, Paul J.; Diao, Minghui; McFarquhar, Greg M.; Patade, Sachin; Phillips, Vaughan; Roberts, Greg C.; Sanchez, Kevin J.; Shi, Yang; Zhang, Meng
Abstract: Global climate models (GCMs) are challenged by difficulties in simulating cloud phase and cloud radiative effect over the Southern Ocean (SO). Some of the new‐generation GCMs predict too much liquid and too little ice in mixed‐phase clouds. This misrepresentation of cloud phase in GCMs results in weaker negative cloud feedback over the SO and a higher climate sensitivity. Based on a model comparison with observational data obtained during the Southern Ocean Cloud Radiation and Aerosol Transport Experimental Study, this study addresses a key uncertainty in the Community Earth System Model version 2 (CESM2) related to cloud phase, namely ice formation in pristine remote SO clouds. It is found that sea spray organic aerosols (SSOAs) are the most important type of ice nucleating particles (INPs) over the SO with concentrations 1 order of magnitude higher than those of dust INPs based on measurements and CESM2 simulations. Secondary ice production (SIP) which includes riming splintering, rain droplet shattering, and ice‐ice collisional fragmentation as implemented in CESM2 is the dominant ice production process in moderately cold clouds with cloud temperatures greater than −20°C. SIP enhances the in‐cloud ice number concentrations (Ni) by 1–3 orders of magnitude and predicts more mixed‐phase (with percentage occurrence increased from 15% to 21%), in better agreement with the observations. This study highlights the importance of accurately representing the cloud phase over the pristine remote SO by considering the ice nucleation of SSOA and SIP processes, which are currently missing in most GCM cloud microphysics parameterizations. Plain Language Summary: For decades, global climate models (GCMs) have exhibited large biases in simulating the radiative budget over the Southern Ocean (SO), mainly due to the poor simulation of SO clouds. Understanding the ice formation processes in SO clouds is critically important to simulating cloud effects on radiation as well as cloud feedback to global warming. In this study, we conduct an integrated model‐observational study to address a key area of uncertainty in GCMs, namely ice formation and evolution over the pristine SO. Model simulations of cloud and aerosol properties are compared against the observational data obtained during the Southern Ocean Cloud Radiation and Aerosol Transport Experimental Study. This study highlights the importance of accurately representing the cloud phase over the pristine remote SO by considering the ice nucleation of sea spray organic aerosols and secondary ice processes, which are currently missing in most GCM cloud microphysics parameterizations. Key Points: Important ice formation processes in Southern Ocean (SO) mixed‐phase clouds are missed by the Community Earth System Model Sea spray organic aerosols contribute a larger fraction of ice nucleating particles over the SO than dust aerosols Secondary ice production processes are crucial for controlling ice crystal concentrations in moderately cold SO clouds